Three-electrode sodium ion soft package battery and preparation method thereof

By using sodium titanium phosphate and carbon coated aluminum foil or stainless steel, and optimizing its structure, the problem of incompatible water systems in the prior art reference electrodes in aqueous sodium ion batteries is solved, and the stable potential is achieved and the battery safety is improved.

CN119542562APending Publication Date: 2025-02-28BENAN ENERGY TECH JIANGSU CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411693897.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When used in aqueous sodium ion battery reference electrodes, the material is incompatible with the water system, resulting in side reactions and battery safety reduction, and it is difficult to provide a stable potential for testing.

Method used

The reference electrode is prepared by sodium titanium phosphate, and the structure is improved, including the use of carbon-coated aluminum foil or stainless steel as the current collector, to enhance the conductivity, and place the reference electrode between the large surface of the core cladding and the inner wall of the aluminum-plastic film to reduce the interference of current changes on the reference potential.

Benefits of technology

The reference electrode is realized to work stably in aqueous sodium ion batteries, providing accurate potential data, reducing the internal resistance of the battery and cell performance loss, and improving the safety of the battery and the reliability of the test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542562A_ABST
    Figure CN119542562A_ABST
Patent Text Reader

Abstract

The invention relates to a three-electrode sodium ion soft package battery and a preparation method thereof, and belongs to the technical field of sodium ion batteries. The preparation method comprises the following steps: S1, laminating a positive plate, a diaphragm and a negative plate according to a Z-shaped sequence, and drying after hot-pressing shaping to obtain a core package; coating the surface of one side of the rectangular first current collector with slurry, drying and compacting to form a slurry layer, and performing insulation treatment on a current collector region which is not covered with the slurry layer to obtain a reference electrode; the slurry comprises titanium sodium phosphate, a first conductive agent, a first binder and a first solvent; the area of the slurry layer in the reference electrode is 80%-90% of the area of the positive plate; the theoretical capacity of the reference electrode is 0.9-1.0 of the area capacity of the positive plate; and S2, attaching a slurry layer of a reference electrode to the positive plate of the core package in the S1 for aluminum plastic film packaging, injecting an electrolyte, sealing, infiltrating, pre-activating, and standing to obtain the three-electrode sodion soft package battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a three-electrode sodium ion soft-pack battery and a preparation method thereof. Background Art

[0002] During the charge and discharge process of sodium-ion batteries, sodium ions are continuously released from and embedded in the positive and negative electrodes to complete the storage and release of capacity. The potential of the positive and negative electrode materials will continue to change during the release and embedding process. By using the reference electrode placed inside the battery, the potential change trend of a single electrode of the entire battery during various tests can be obtained. This potential change information is important data for researchers to analyze material structure and improve processes.

[0003] The commonly used metal wire sodium plating method for sodium ion battery reference electrodes has a short lifespan and a loose sodium plating structure, which cannot be used for long-term monitoring. Another method of connecting the end of the metal wire to a sodium sheet is also limited by the internal resistance of the metal wire, resulting in increased measurement errors. Chinese invention patent CN 115241553 A introduces a reference battery cavity as a reference electrode placement area. Although it can effectively increase the sodium content of the reference electrode and extend the service life, the actual operation of wetting the foam metal skeleton with sodium metal is complicated. In addition to the filamentary reference electrode, the foil-like and mesh structures and the placement positions include between diaphragms and between pole ears. These factors will further affect the stability and reliability of the reference potential and still need to be improved.

[0004] In addition to structural issues, the reference electrode must first ensure that its own reference potential can remain stable for a long time and will not fluctuate greatly during the test. Sodium metal, which is widely used in button half-cell electrodes, is an ideal material for sodium-ion battery reference electrodes, but sodium metal reference electrodes are not suitable for sodium-ion batteries that contain a lot of structural water or use aqueous electrolytes. Sodium reacts with water to produce gas, which not only destroys the stability of the reference potential, but also causes battery swelling, seriously reducing safety. There are currently no related reports in the existing technology.

[0005] In order to meet the requirements of the production of reference electrodes for aqueous sodium-ion batteries, the material must be compatible with the water system and will not produce side reactions with water to damage the battery itself after being placed inside the battery. At the same time, it can provide a stable potential within a certain period of time so that the changes in the positive and negative electrode potentials during the test can be accurately measured. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a three-electrode sodium ion soft pack battery and a preparation method thereof. By using sodium titanium phosphate to prepare a reference electrode and improving the structure of the reference electrode, a reference electrode that can be applied to an aqueous sodium ion battery system and provides a stable potential is provided. The main process is to coat a slurry prepared from sodium titanium phosphate, a conductive agent, a binder and a solvent on a current collector, and form a slurry layer of a certain thickness after drying and compacting. The current collector area not covered with the slurry layer is insulated with an insulating tape, and then placed between the core package and the aluminum-plastic film interlayer and fixed with an insulating tape. Then, the aluminum-plastic film is encapsulated with the core package and the electrolyte is vacuum injected and sealed. Finally, a small current is charged to pre-activate the reference electrode by inserting sodium titanium phosphate to its potential platform, thereby obtaining a three-electrode sodium ion soft pack battery with a reference electrode having a stable potential.

[0007] The first object of the present invention is to provide a method for preparing a three-electrode sodium ion soft pack battery, comprising the following steps:

[0008] S1, stacking the positive electrode sheet, the separator, and the negative electrode sheet in a Z-shaped order, hot pressing and shaping, and then drying to obtain a core package; wherein the number of positive electrode sheets and negative electrode sheets is the same;

[0009] A slurry is coated on one side of a rectangular first current collector, dried and compacted to form a slurry layer, and the current collector area not covered with the slurry layer is insulated to obtain a reference electrode; the slurry comprises sodium titanium phosphate, a first conductive agent, a first binder and a first solvent in parts by mass; the area of ​​the slurry layer in the reference electrode is 80%-90% of the area of ​​the positive electrode sheet; the theoretical capacity of the reference electrode is 0.9-1.0 of the area capacity of the positive electrode sheet;

[0010] S2. The slurry layer of the reference electrode described in S1 is bonded to the positive electrode sheet of the core package described in S1 to perform aluminum-plastic film packaging, and the electrolyte is injected and sealed. After infiltration, pre-activation is performed and the battery is allowed to stand to obtain the three-electrode sodium ion soft-pack battery.

[0011] In one embodiment of the present invention, in S1, the slurry includes, by mass, 30-60 parts of sodium titanium phosphate, 2-10 parts of a first conductive agent, 2-10 parts of a first binder, and 20-66 parts of a first solvent.

[0012] In one embodiment of the present invention, in S1, the method for preparing the positive electrode sheet and the negative electrode sheet comprises the following steps:

[0013] S11, respectively mixing the positive and negative electrode active materials, the second conductive agent, the second binder and the second solvent to obtain positive and negative electrode slurries;

[0014] S12, coating the positive and negative electrode slurries on the second current collector respectively, and obtaining the positive and negative electrode sheets respectively through drying and rolling.

[0015] In one embodiment of the present invention, in S11, the positive electrode active material is selected from one or more of a polyanion compound, a layered oxide and a Prussian blue compound; preferably, the positive electrode active material is a Prussian blue compound, and the Prussian blue compound has a general formula of Na b M1 d M2 c [Fe(CN)6]·mH2O, 0<b≤2, 0≤d≤1, 0≤c<1, c+d=1, 0<m≤3, wherein M1 is selected from one or more of manganese, iron, cobalt and nickel, and M2 is selected from zinc and / or copper, because the Prussian blue compound itself contains water of crystallization.

[0016] And / or, the negative electrode active material is one or more of titanium-based phosphates, carbon-based materials and Prussian blue compounds.

[0017] And / or, the mass ratio of the positive and negative electrode active materials, the second conductive agent, the second binder and the second solvent is 90-95:2-8:1-5:130-170.

[0018] In one embodiment of the present invention, the first conductive agent and the second conductive agent are independently selected from one or more of carbon nanotubes, acetylene black, conductive carbon black, conductive graphite, carbon fiber and graphene.

[0019] In one embodiment of the present invention, the first binder and the second binder are independently selected from one or more of polyolefins, fluorine-containing resins, polypropylene resins and rubbers, for example, they may be one or more of polyvinylidene fluoride, styrene rubber, nitrile rubber, styrene-butadiene rubber (SBR), polyacrylamide (PAA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyimide (PI), butadiene rubber, modified butadiene rubber, carboxyl-modified styrene-butadiene rubber and modified polyorganosiloxane polymers.

[0020] In one embodiment of the present invention, the first solvent and the second solvent are independently selected from one or more of N-methyl-2-pyrrolidone, ethanol and acetone.

[0021] In one embodiment of the present invention, in S1, the insulating material is selected from polypropylene tape or polyimide tape.

[0022] In one embodiment of the present invention, in S2, the soaking temperature is 40°C-45°C, and the soaking time is 22h-26h.

[0023] In one embodiment of the present invention, in S2, the pre-activation is charging at 0.01C-0.1C to 70%-90% of the capacity of the reference electrode.

[0024] In one embodiment of the present invention, in S2, the standing time is 60 min-120 min.

[0025] In one embodiment of the present invention, in S2, the aluminum-plastic film needs to be punched before use, and the total depth of the punched holes is increased by 0.20 mm in thickness of the core package after hot pressing, so as to ensure that the core package containing the reference electrode and the aluminum-plastic film can fit tightly.

[0026] In one embodiment of the present invention, the first current collector and the second current collector are independently selected from carbon-coated aluminum foil or carbon-coated stainless steel.

[0027] In one embodiment of the present invention, the process further includes preparing the tabs, welding the positive tabs to the positive electrode sheet of the core package, welding the negative tabs to the negative electrode sheet of the core package, and welding the reference tabs to the reference electrode.

[0028] In one embodiment of the present invention, the positive electrode tab, the negative electrode tab and the reference electrode tab are exposed from the aluminum-plastic film, the positive electrode tab and the negative electrode tab are led out in the same direction, and the reference electrode tab is led out in the opposite direction of the positive and negative electrode tabs.

[0029] The second object of the present invention is to provide a three-electrode sodium ion soft-pack battery prepared by the method described.

[0030] The technical solution of the present invention has the following advantages over the prior art:

[0031] (1) The preparation method described in the present invention uses sodium titanium phosphate to prepare a reference electrode, and utilizes the characteristic of sodium titanium phosphate having a stable potential within a certain capacity range to ensure the accuracy of the reference electrode potential; and utilizes the characteristic of sodium titanium phosphate being compatible with aqueous electrolytes to adjust the type of current collector so that it can be applied in aqueous sodium ion batteries.

[0032] (2) The preparation method described in the present invention uses aluminum foil or stainless steel coated with a carbon layer as the current collector of the reference electrode, and the carbon layer increases the conductivity of the reference electrode and reduces the contact internal resistance of the reference electrode.

[0033] (3) The preparation method described in the present invention places the reference electrode between the large surface of the core package and the inner wall of the aluminum-plastic film, and leads the reference electrode tab toward the opposite side of the positive and negative electrodes, which can reduce the interference of current changes on the reference potential and avoid the obstruction of ion transmission between the positive and negative electrodes caused by the reference electrode, thereby effectively reducing the fluctuation of the reference potential and the loss of battery cell performance.

[0034] (4) The preparation method described in the present invention places the reference electrode between the large surface of the core package and the inner wall of the aluminum-plastic film, and directs the reference electrode tab to the opposite side of the positive and negative electrodes, which can reduce the interference of current changes on the reference potential and avoid the obstruction of ion transmission between the positive and negative electrodes caused by the reference electrode, thereby effectively reducing the fluctuation of the reference potential and the loss of battery cell performance.

[0035] (5) The reference electrode structure in the three-electrode sodium ion soft pack battery of the present invention can be widely applied to sodium ion soft pack batteries of polyanion, Prussian blue, layered oxide system, etc. It is used to monitor the potential changes of the positive and negative electrodes during the charge and discharge process of the sodium ion battery, and provide important data support for improving the performance of the sodium ion battery and optimizing the battery cell design through performance tests such as cycle and impedance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0037] Figure 1 is a schematic structural diagram of a reference electrode of the present invention;

[0038] Figure 2 It is a schematic structural diagram of the three-electrode sodium ion soft-pack battery of the present invention. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.

[0040] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.

[0041] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.

[0042] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.

[0043] In the present invention, unless otherwise specified, the separator used in the embodiments of the present invention is a polyethylene separator with a thickness of 10 μm.

[0044] In the present invention, unless otherwise specified, the concentration of the electrolyte used in the embodiments of the present invention is 1 mol / L, and the electrolyte is prepared by dissolving sodium perchlorate in ethylene carbonate.

[0045] Example 1

[0046] Reference Figure 1-Figure 2 As shown, the three-electrode sodium ion soft pack battery and the preparation method thereof of this embodiment specifically include the following steps:

[0047] S1. Preparation of core package

[0048] S11, preparation of positive and negative electrode slurry: weigh 92.0g of positive and negative electrode active materials (the positive electrode active material is Na 1.83 Mn 0.7 Cu 0.3 [Fe(CN)6]·2.7H2O, the negative electrode active material is Na 1.7 Mn[Mn(CN)6]·2.4H2O, 4.0g conductive carbon black, 1g conductive carbon nanotube powder, 3.0g binder polyvinylidene fluoride powder, 150g solvent N-methyl-2-pyrrolidone, put into a ball mill and mill at 40rpm for 180min to obtain positive and negative electrode slurries respectively;

[0049] S12, preparation of positive and negative electrode sheets: pour the positive and negative electrode slurries into the material tank of the transfer coater, control the transfer die head to perform double-sided coating on the carbon-coated aluminum foil with a thickness of 14 μm, dry in an oven at 130°C, and then use a roller press with a roller pressure of 4.0 MPa to roll and die-cut to obtain a positive electrode sheet with a size of 69 mm×55 mm and a negative electrode sheet with a size of 65 mm×53 mm;

[0050] S13, preparation of core package: stack the positive electrode sheet, separator and negative electrode sheet in a Z-shaped order, with the outer layer being the positive electrode sheet (12 layers for the positive electrode sheet and 12 layers for the negative electrode sheet), the outermost layer and the side are covered with separator and fixed with polypropylene tape, and after hot pressing and shaping, the aluminum tabs are ultrasonically welded to the positive and negative tabs respectively, and then the moisture is dried and transferred to the glove box and sealed in a ziplock bag for storage;

[0051] S2. Preparation of aluminum-plastic film: The thickness of the core package is measured by a micrometer to be 2.82 mm, and 0.20 mm is added to the thickness to calculate the total depth of the aluminum-plastic film. The aluminum-plastic film is punched by a punching machine, and the punched aluminum-plastic film is transferred to a glove box for standby use;

[0052] S3. Preparation of reference electrode:

[0053] S31, preparation of slurry: 45.0 g of sodium titanium phosphate, 4.0 g of conductive carbon black, 1.0 g of carbon nanotube dry powder, 2 g of polyvinylidene fluoride dry powder, and 60 g of solvent N-methyl-2-pyrrolidone are mixed uniformly to obtain slurry;

[0054] S32. Preparation of reference electrode: Use an automatic coating device to coat the slurry on one side of a carbon-coated aluminum foil with a size of 70 mm × 50 mm and a thickness of 14 μm, with a blank area width of 6 mm. After drying and compaction, ultrasonically weld the aluminum pole ear in the middle of the blank area, use polypropylene tape to insulate the blank area and the back, and then appropriately trim the tape along the cut edge of the carbon-coated aluminum foil, with the cut edge of the tape 1 mm-2 mm away from the cut edge of the foil, to obtain a reference electrode; wherein, the area of ​​the slurry layer (dressing area) in the reference electrode is 85% of the area of ​​the positive electrode sheet, and the theoretical capacity of the reference electrode is calculated based on the area of ​​the dressing area, the surface density, the mass of active substances and the gram capacity to be 0.95 of the area capacity of the positive electrode sheet;

[0055] S4. Preparation of three-electrode sodium ion soft-pack battery: the slurry layer of the reference electrode is opposite to the large center of the positive electrode sheet of the core package, the lead-out direction of the reference tab is on the opposite side of the lead-out direction of the positive and negative tabs, and it is fixed with polypropylene tape and placed in the punching hole of the aluminum-plastic film. The aluminum-plastic film shell is combined, and the heat sealer is used to package in the glove box, and then each tab is wrapped with polypropylene tape for insulation treatment, 6g of electrolyte is injected, and vacuum sealing is performed; after the liquid is injected, the positive-negative, positive-reference, and negative-reference voltages and internal resistances are measured using an AC internal resistance meter, and after checking that there is no internal short circuit and voltage abnormality, it is placed at 45°C for immersion for 24 hours; after the immersion is completed, the three-electrode soft-pack battery is loaded with a fixture, the clamping force is set to 300kg, the reference electrode of the three-electrode soft-pack battery is connected to the positive electrode of the test cabinet, and the negative electrode is connected to the negative electrode of the test cabinet for pre-activation, and a constant current charging step is set, and it is charged to 80% of the reference electrode capacity at a constant current of 0.1C. After the pre-charging is completed, it is placed at room temperature for 60 minutes to obtain a three-electrode sodium ion soft-pack battery.

[0056] Comparative Example 1

[0057] It is basically the same as Example 1, except that the area of ​​the slurry layer (dressing area) in the reference electrode is 85% of the area of ​​the positive electrode sheet; the theoretical capacity of the reference electrode is 0.3 of the area capacity of the positive electrode sheet.

[0058] Comparative Example 2

[0059] Basically the same as Example 1, except that: the area of ​​the slurry layer (dressing area) in the reference electrode is 85% of the area of ​​the positive electrode; the theoretical capacity of the reference electrode is 1.5 of the area capacity of the positive electrode.

[0060] Comparative Example 3

[0061] Basically the same as Example 1, except that: the area of ​​the slurry layer (dressing area) in the reference electrode is 20% of the area of ​​the positive electrode; the theoretical capacity of the reference electrode is 0.95 of the area capacity of the positive electrode.

[0062] Comparative Example 4

[0063] The method is basically the same as Example 1, except that the battery is charged at a constant current of 0.1C to 20% of the reference electrode capacity.

[0064] Comparative Example 5

[0065] Basically the same as Example 1, except that: charging at a constant current of 0.1C to 100% of the reference electrode capacity.

[0066] Comparative Example 6

[0067] The method is basically the same as Example 1, except that the slurry is replaced with 0.2 g of sodium metal, and specifically includes the following steps:

[0068] Preparation of reference electrode: Cut the carbon-coated aluminum foil to 70 mm × 50 mm in size and 14 μm in thickness, with a blank area of ​​6 mm in width, ultrasonically weld the aluminum pole ear in the middle of the blank area, then transfer it to the glove box, use polytetrafluoroethylene tweezers to place 0.2 g of sodium metal in the middle area of ​​the carbon-coated aluminum foil and press lightly to make the sodium metal stick to the carbon-coated aluminum foil, place it in a ziplock bag and squeeze it by hand to exhaust and seal it; then place the ziplock bag on the hot-pressed metal plate, the aluminum pole ear at the welding point of the carbon-coated aluminum foil does not extend into the metal plate, adjust the temperature of the hot press to 50 ° C and the pressure to 0.6 MPa and press for 30 seconds. , so that the sodium metal is completely attached to the carbon-coated aluminum foil. After the hot pressing is completed, the ziplock bag is transferred to the glove box, the ziplock bag is torn off and the edge of the carbon-coated aluminum foil is trimmed. The blank area and the back are insulated with polypropylene tape, and then the tape is appropriately trimmed along the cut edge of the carbon-coated aluminum foil. The cut edge of the tape is 1mm-2mm away from the cut edge of the foil to obtain a reference electrode; wherein, the area of ​​the slurry layer (dressing area) in the reference electrode is 85% of the area of ​​the positive electrode sheet. The theoretical capacity of the reference electrode is calculated based on the area, surface density, active substance mass and gram capacity of the dressing area to be 0.95 of the area capacity of the positive electrode sheet.

[0069] Test Example 1

[0070] After infiltration, the voltage and internal resistance of the positive electrode to the negative electrode, the positive electrode to the reference electrode, and the negative electrode to the reference electrode were measured using an AC internal resistance meter. The results are shown in Table 1:

[0071] Table 1

[0072]

[0073]

[0074] As can be seen from Table 1, the area of ​​the slurry layer in the reference electrode facing the positive electrode sheet and the capacity ratio to the positive electrode have a great influence on the accuracy and stability of the reference electrode. In Comparative Example 1, the contact internal resistance of the reference electrode is reduced due to the reduced thickness of the slurry layer. In Comparative Example 2, the contact internal resistance is significantly increased due to the thick thickness of the required slurry layer. In Comparative Example 3, since the area of ​​the reference electrode is relatively small, in order to ensure the capacity, the required slurry layer thickness is significantly thicker (thicker than Comparative Example 2), resulting in a significant increase in the contact internal resistance. At the same time, due to the small area, it is not fully fitted, affecting the subsequent reference potential stability. Comparative Examples 4 and 5 are not much different in the initial assembly, but the long-term cycle performance is unstable in the later period. In Comparative Example 6, due to the use of metallic sodium for the reference electrode, its internal resistance is significantly reduced, resulting in abnormal battery cycles in long-term cycles.

[0075] Test Example 2

[0076] The three-electrode sodium ion soft-pack batteries of Example 1 and Comparative Examples 1-6 were subjected to 2 cycles of constant current charge and discharge at room temperature with a small current (0.1C) to activate the battery, and then the cycle (10C), rate and other performance tests were performed. During the test, the voltage terminals were always connected to the positive electrode-reference electrode and the negative electrode-reference electrode respectively for monitoring the independent potential of the positive and negative electrodes. The stability test results of the reference electrode monitoring in the long-term cycle are shown in Table 2:

[0077] Table 2

[0078]

[0079]

[0080] As can be seen from Table 2, the reference potential of the embodiment did not fluctuate abnormally. The reference potential of the embodiment had the longest stabilization time, while comparative examples 1-3 all experienced abnormal fluctuations after 100 hours, comparative examples 4-5 experienced monitoring anomalies due to insufficient activation of the reference electrode, and comparative example 6 had a sharply shortened stabilization time due to the destruction of the sodium electrode.

[0081] In summary, the reference electrode capacity of Comparative Example 1 is much lower than that of Example 1, and the thickness of the slurry layer is reduced. Although the contact internal resistance of the reference electrode is reduced, the reference electrode capacity of Comparative Example 1 is relatively low. Under long-term monitoring conditions, the potential of the reference electrode is difficult to maintain in a stable range due to the micro-current consumption of the voltage terminal, and the voltage monitoring stabilization time is lower than that of Example 1.

[0082] In comparative example 2, the capacity of the reference electrode exceeds the single-sided capacity of the positive electrode. During the pre-charging process, not only is it difficult for the sodium titanium phosphate of the reference electrode to reach a stable SOC range, but the excessive voltage caused by over-discharge of the positive electrode sheet affects the stability of the electrolyte. At the same time, since the required slurry layer thickness is relatively thick, the contact internal resistance increases significantly, which is not conducive to maintaining its own potential stability.

[0083] In Comparative Example 3, since the reference electrode area is relatively small, in order to ensure the capacity, the required slurry layer thickness is significantly thicker (thicker than Comparative Example 2), resulting in a significant increase in contact internal resistance. During the monitoring process, the potential stability is shorter than that of Example 1.

[0084] The pre-charge capacity of comparative example 4 is relatively low. In the low capacity range, as the capacity of the reference electrode is consumed, the potential of sodium titanium phosphate fluctuates greatly, affecting the accuracy of the reference potential.

[0085] In comparative example 5, the pre-charge capacity reaches 100%, and the potential of sodium titanium phosphate drops too much at too high a capacity, affecting the accuracy of the reference potential.

[0086] In comparative example 6, during the long-term circulation process, the structural water in the Prussian blue was precipitated to destroy the sodium metal gas production, and the core package was obviously swollen, which could not be monitored for a long time.

[0087] Test Example 3

[0088] Reference electrodes were prepared using Example 1 and Comparative Example 6, and soft-pack batteries with different positive and negative active materials were tested. The voltage terminals were always connected to the positive electrode-reference electrode and the negative electrode-reference electrode to monitor the independent potential of the positive and negative electrodes. The test results of the stability of the reference electrode monitoring in long-term cycles are shown in Table 3:

[0089] Table 3

[0090]

[0091] It can be seen from Table 3 that the reference electrode scheme of the present invention exhibits good potential stability in the potential detection of sodium ion batteries of different systems. This is mainly because the sodium titanium phosphate active material used in the reference electrode has a stable potential under a suitable SOC (the theoretical capacity of the reference electrode is 0.9-1.0 of the positive electrode area capacity), while the sodium electrode as a conventional reference electrode reacts with metallic sodium due to trace water in the electrode, causing battery failure, thereby causing instability in the monitored potential.

[0092] Both the positive active material and the negative active material adopt Prussian blue, and the monitoring potential stabilization time of Example 1 is as long as 382 hours; while the reference electrode of Comparative Example 6 is less than 20 hours; both the positive active material and the negative active material adopt polyanions, and the monitoring potential stabilization time of Example 1 is 415 hours, while the reference electrode of Comparative Example 6 is less than 120 hours; after the positive active material and the negative active material adopt polyanions and hard carbon materials, the monitoring potential stabilization time of Example 1 is 358 hours; while the reference electrode of Comparative Example 6 does not exceed 100 hours; after the positive active material and the negative active material adopt layered oxides and hard carbon materials, the monitoring potential stabilization time of Example 1 is 378 hours, while the reference electrode of Comparative Example 6 still performs poorly and fails to break through 100 hours.

[0093] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a three-electrode sodium ion soft pack battery, characterized in that: The following steps are involved: S1, stacking the positive electrode sheet, the separator, and the negative electrode sheet in a Z-shaped order, hot pressing and shaping, and then drying to obtain a core package; wherein the number of positive electrode sheets and negative electrode sheets is the same; A slurry is coated on one side of a rectangular first current collector, dried and compacted to form a slurry layer, and the current collector area not covered with the slurry layer is insulated to obtain a reference electrode; the slurry includes sodium titanium phosphate, a first conductive agent, a first binder and a first solvent; the area of ​​the slurry layer in the reference electrode is 80%-90% of the area of ​​the positive electrode sheet; the theoretical capacity of the reference electrode is 0.9-1.0 of the area capacity of the positive electrode sheet; S2. The slurry layer of the reference electrode described in S1 is bonded to the positive electrode sheet of the core package described in S1 to perform aluminum-plastic film packaging, and the electrolyte is injected and sealed. After infiltration, pre-activation is performed and the battery is allowed to stand to obtain the three-electrode sodium ion soft-pack battery.

2. The method for preparing a three-electrode sodium ion soft pack battery according to claim 1, characterized in that: In S1, the method for preparing the positive electrode sheet and the negative electrode sheet comprises the following steps: S11, respectively mixing the positive and negative electrode active materials, the second conductive agent, the second binder and the second solvent to obtain positive and negative electrode slurries; S12, coating the positive and negative electrode slurries on the second current collector respectively, and obtaining the positive and negative electrode sheets respectively through drying and rolling.

3. The method for preparing a three-electrode sodium ion soft pack battery according to claim 1, characterized in that: In S1, the insulating material is selected from polypropylene tape or polyimide tape.

4. The method for preparing a three-electrode sodium ion soft pack battery according to claim 1, characterized in that: In S2, the soaking temperature is 40°C-45°C, and the soaking time is 22h-26h.

5. The method for preparing a three-electrode sodium ion soft pack battery according to claim 1, characterized in that: In S2, the pre-activation is to charge the reference electrode at 0.01C-0.1C to 70%-90% of its capacity.

6. The method for preparing a three-electrode sodium ion soft pack battery according to claim 1, characterized in that: In S2, the standing time is 60 min-120 min.

7. The method for preparing a three-electrode sodium ion soft pack battery according to claim 1, characterized in that: The first current collector and the second current collector are independently selected from carbon-coated aluminum foil or carbon-coated stainless steel.

8. The method for preparing a three-electrode sodium ion soft pack battery according to claim 1, characterized in that: It also includes the preparation of the tabs, welding the positive tab to the positive electrode sheet of the core package, welding the negative tab to the negative electrode sheet of the core package, and welding the reference tab to the reference electrode.

9. The method for preparing a three-electrode sodium ion soft pack battery according to claim 8, characterized in that: The positive electrode tab, the negative electrode tab and the reference electrode tab are exposed from the aluminum-plastic film, the positive electrode tab and the negative electrode tab are led out in the same direction, and the reference electrode tab is led out in the opposite direction to the positive and negative electrode tabs.

10. A three-electrode sodium ion soft pack battery prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Three-electrode structure of sodium ion battery and manufacturing method of three-electrode structure

    CN115241553A